Checklist and new species of caddisfly (Insecta: Trichoptera) from Roraima state, Brazil - Gama Neto, Jaime de Liege; Pes, A. M.; Hamada, Neusa (Zootaxa, 2017)
We conducted an inventory of the Trichoptera fauna of Serra do Tepequém, Amajari municipality (county), Roraima state, Brazil. Adult caddisflies were collected with Pennsylvania and Malaise traps operated beside three 2nd-order streams near the summit of Serra do Tepequém. We identified 27 Trichoptera species (including two new species), all representing new records for the state of Roraima, five of these species are recorded for the first time in Brazil. In this study, two new species are described: Marilia mahedae sp. nov. differs from all other species of the genus by the following combination of characters: Segment X subquadrate in dorsal view, bipartite, membranous mesally, with short apical V-shaped incision; preanal appendages wide at base in lateral view; endotheca with an acute subapicoventral projection, directed anterad in lateral view; phallotheca very short. Polyplectropus tepequemensis sp. nov. differs from all other species of the genus by the following combination of characters: Posterior margin of sternum IX nearly straight; slightly sclerotized intermediate appendages broad in the basal 2/3 and abruptly slender apically; two phallic ducts, each with an endothecal spine. With this inventory the number of Trichoptera species for Roraima state increased from 37 to 65. Copyright © 2017 Magnolia Press.
Keywords: Animals; Animals Dispersal; Holometabola; Insect; Animals Distribution; Animal; Holometabola; Insecta